7(х-2)=6(х+1)
7х-14=6х+6
7х-6х=14+6
х=20
ответ: 20
3х-2=5х-6
6-2=5х-3х
4=2х
х=4:2
х=2
ответ: 2
0,5(3х-4)+4,4=0,9(4х-2)
1,5х-2+4,4=3,6х-1,8
2,4+1,8=3,6х-1,5х
4,2=2,1х
х=4,2:2,1
Объяснение:
1)7(х - 2) = 6(х + 1)
7x-14=6x+6
7x-14-6x-6=0
x-20=0
x=20
2)3x - 2 = 5x - 6
3x-2-5x+6=0
-2x+4=0
-2x=-4
x=2
3)0,5(3х - 4) + 4,4 = 0,9(4х - 2)
1.5x-2+4.4=3.6x-1.8
1.5x-2+4.4-3.6x+1.8=0
-2.1x+4.2=0
7(х-2)=6(х+1)
7х-14=6х+6
7х-6х=14+6
х=20
ответ: 20
3х-2=5х-6
6-2=5х-3х
4=2х
х=4:2
х=2
ответ: 2
0,5(3х-4)+4,4=0,9(4х-2)
1,5х-2+4,4=3,6х-1,8
2,4+1,8=3,6х-1,5х
4,2=2,1х
х=4,2:2,1
х=2
ответ: 2
Объяснение:
1)7(х - 2) = 6(х + 1)
7x-14=6x+6
7x-14-6x-6=0
x-20=0
x=20
2)3x - 2 = 5x - 6
3x-2-5x+6=0
-2x+4=0
-2x=-4
x=2
3)0,5(3х - 4) + 4,4 = 0,9(4х - 2)
1.5x-2+4.4=3.6x-1.8
1.5x-2+4.4-3.6x+1.8=0
-2.1x+4.2=0
x=2